Aktivitas Antibakteri Ekstrak Air, Etanol, Kloroform Teh Hijau (Camelia Sinensis L.) Terhadap Pertumbuhan Stophylococcus Epidermis - Salwa Pratiwi; Ahwan; Fadilah Qonitah (An-Najat, 2024)
Acne is a skin condition that often occurs on the face, neck, chest, and back. The oil glands in the skin are very active, causing the skin pores to become clogged with fat deposits. One of the factors causing acne is Staphylococcus epidermis bacterial infection, and skin conditions. Alternative treatments used are plants that have benefits as antibacterials. This study was experimental in nature, the aim of which was to determine the differences in the antibacterial activity test of Water Extract (EA), Ethanol Extract (EE), and Chloroform Extract (EK) of green tea leaves (Camellia Sinensis.L) against the growth of Staphylococcus epidermis bacteria. The disc diffusion method was used in testing antibacterial activity. The results showed that each positive extract had antibacterial activity against Staphylococcus epidermis bacteria with different levels of inhibition. The strong inhibition category is owned by EE 40% (12.41 ± 0.20) mm, EE 60% (14.4 ± 0.23) mm, EK 40% (11.5 ± 0.31) mm, and EK 60% (13.3 ± 0.1) mm. The moderate inhibition category is owned by EA 10%, (6.38 ± 0.15), EA 40% (8.53 ± 0.28), EA 60% (9.36 ± 0.21), EE 10% (9.76 ± 0.18) mm, and EK 10% (7.38 ± 0.20) mm. Meanwhile, the positive control of clindamycin 1.5% had a very strong inhibitory power with an average of (30.83 ± 0.10) mm, and the negative control of DMSO 1% had a weak inhibitory power of (0.00 ± 0.00). Based on the results of the study, it can be concluded that water, ethanol and chloroform extracts of green tea leaves have been proven to have antibacterial activity against Staphylococcus epidermis bacteria which are significantly different (p value 0.000 <0.05).